Unlocking Islamic Consumer Behaviour on Gen Z: The Impact of E-Wallet Usage, Lifestyle, and Self Control - Saputri, Indri Ayu; Fajri AF, Muh Shadiqul; Villaruel, Angelita S. (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study aims to examines the impact of e-wallet usage, lifestyle, and self-control on the Islamic islamic consumption behavior of Generation Z. By integrating these factors, it seeks to offer insights into consumer behavior from an Islamic perspective.Design/methodology: A quantitative explanatory research design was employed, targeting Generation Z in Samarinda. Data were collected via purposive sampling, with 100 respondents who actively use e-wallets. The study utilized ordinal logistic regression to analyze the influence of the independent variables (e-wallet usage, lifestyle, self-control) on the dependent variable (Islamic consumption behavior).Findings: E-wallet usage significantly affects Islamic consumption behavior, where its convenience often leads to both adherence and deviations from Islamic principles. Lifestyle, however, demonstrated a negative and insignificant effect on Islamic consumption behavior, indicating that it does not strongly influence adherence to Islamic principles in this context. Self-control emerges as a pivotal factor, positively correlating with adherence to Islamic consumption principles, mitigating excessive spending, and aligning with religious values.Practical implications: The findings provide practical insights for stakeholders, including policymakers and marketers, to foster Islamic consumption behavior by promoting ethical e-wallet features, enhancing awareness of lifestyle impacts, and strengthening self-control mechanisms.Originality/Value: This research offers a novel perspective by integrating lifestyle, self-control, and e-wallet usage within the framework of Islamic consumption behavior, contributing theoretical and practical knowledge to consumer behavior studies in a digital era.